Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.12659/msm.906954
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Vascular Endothelial Growth Factor (VEGF) Antibody Ameliorates Cartilage Degradation in a Rat Model of Chronic Sports Arthritic Injury

Abstract: BackgroundAlthough a relationship between vascular endothelial growth factor (VEGF) and articular cartilage degeneration has been reported, little is known regarding its role in articular cartilage injury induced by sports activities. In this study, we evaluated the role of VEGF in a rat model of chronic sports arthritic injury.Material/MethodsAnimals were divided into 3 groups: Control (n=10), Vehicle (chronic sports arthritic injury, n=10), and Bevacizumab (chronic sports arthritic injury treated with anti-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Inflammation during early-stage OA is induced by cytokines, especially TNF-α and IL-1β [31]. In consistence with recent results [32], the present study showed that the levels of TNF-α and IL-1β were elevated in the knee synovial fluid of model rats. However, miR-30b-5p down-regulation decreased the levels of IL-1β and TNF-α in model rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Inflammation during early-stage OA is induced by cytokines, especially TNF-α and IL-1β [31]. In consistence with recent results [32], the present study showed that the levels of TNF-α and IL-1β were elevated in the knee synovial fluid of model rats. However, miR-30b-5p down-regulation decreased the levels of IL-1β and TNF-α in model rats.…”
Section: Discussionsupporting
confidence: 90%
“…Inflammation during early-stage OA is induced by cytokines, especially TNF-α and IL-1β [31]. In consistence with recent results [32], the present study showed that the levels of TNF-α and IL-1β were elevated in the knee synovial fluid of This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Discussionsupporting
confidence: 88%
“…In a traumatic brain injury model, mice treated with Bevacizumab had a significant drop in TNF-α levels, highlighting the ability of Bevacizumab to reduce inflammatory processes and subsequent vascular complications [27]. This anti-inflammatory feature of Bevacizumab was also confirmed in rats subjected to chronic sports arthritic injuries by reducing the levels of TNF-α [28].…”
Section: Effect Of Bevacizumab On Tnf-αmentioning
confidence: 76%
“…It is generally believed that there is a close relationship between angiogenesis and osteogenesis [11,[23][24][25][26]. In the process of articular cartilage degeneration, hypertrophic chondrocytes enable microvessels to grow into the growth Journal of Nanomaterials plate by secreting angiogenic factors, such as VEGF, which leads to cartilage absorption and bone formation [27,28]. During bone repair, microvessels provide a prerequisite for the exchange of oxygen and nutrients for bone regeneration [23].…”
Section: Discussionmentioning
confidence: 99%